2021
DOI: 10.1155/2021/9971353
|View full text |Cite
|
Sign up to set email alerts
|

P3H4 Overexpression Serves as a Prognostic Factor in Lung Adenocarcinoma

Abstract: Background. The present study is aimed at evaluating the functional and clinical values of P3H4 in lung adenocarcinoma. Moreover, we also investigated the downstream pathways that P3H4 might participate in. Methods. The differential expression analysis was used to identify genes differentially expressed in lung adenocarcinoma tissues as compared with normal tissues. Survival analysis was used to test the association between P3H4 and survival time. Gene set enrichment analysis was conducted to explore the downs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Physiologically, P3H4 is a prognostic factor for lung adenocarcinoma and bladder cancer ( Li et al. , 2018 ; Jin et al. , 2021 ); it contributes to cancer invasion and growth ( Hao et al.…”
Section: Discussionmentioning
confidence: 99%
“…Physiologically, P3H4 is a prognostic factor for lung adenocarcinoma and bladder cancer ( Li et al. , 2018 ; Jin et al. , 2021 ); it contributes to cancer invasion and growth ( Hao et al.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed the potential of these genes. Overexpression of P3H4 indicated a poor prognosis in lung adenocarcinoma (31). In addition, AP2S1 was confirmed as a risk factor and was correlated with immune infiltration in triple-negative breast cancer (32).…”
Section: Discussionmentioning
confidence: 85%
“…The last two ECM proteins are involved in the stability of collagen intermolecular crosslinks. The expression of P3h4, which encodes a protein catalyzing the hydroxylation of lysine residues in collagen alpha chains, was reported to be a predictor of poor overall survival in both bladder [40] and lung cancer [41]. PLOD2, which provides attachment sites for carbohydrates in collagen, was also initially reviewed as a potential prognostic factor [42].…”
Section: Discussionmentioning
confidence: 99%